Development of equations through trajectories linearization for an HEPWM inverter - Azli, N. A. (2006)
Harmonic elimination pulse width modulation (HEPWM) is an inverter control technique that eliminates specific harmonics of its output voltage by controlling switching signals at certain switching angles. This method offer less losses in the inverter switches since the switching frequency is 40% lower than the typical sinusoidal pulse width modulation (SPWM) technique. However, as the equations to calculate the switching angles based on the HEPWM technique are too complex to be solved online by microprocessors, simpler solutions for the switching angles are required. Simplified solutions through trajectories linearization for the HEPWM technique are proposed in this paper. A set of equations for the HEPWM technique switching angles solutions suitable for microprocessor implementation are derived and then tested for accuracy and performance through simulation using MATLAB/Simulink.